Protocol for systematic review and meta-analysis on randomized clinical trials for direct oral anticoagulant in subjects with acute coronary syndrome. - El Khidir, Israa Y.; Elnour, Asim Ahmed; Al Amoodi, Abdulla; Alrashdi, Abrar Ayad; Almansour, Haifa Hamoud; Almarwani, Teif Abdulkarim; Alrowaili, Shahad Fayad; Al Khudhairy, Shouq Lutfi; Alshammari, Asma Faisal; Sadeq, Adel; Al Mazrouei, Nadia; Al-Kubaisi, Khalid Awad; et al. (Pharmacy Practice (1886-3655))
Background: Recently, direct oral anticoagulant (DOAC) has been projected for secondary prevention of recurrent ischemic events post-acute coronary syndrome (ACS). The addition of a DOAC to the antiplatelet regimen of subjects with the ACS is clinically practiced in candidates where compelling anticoagulation is indicated by high thromboembolic risk. The current evidence provides approved compelling indication for the DOAC, particularly for rivaroxaban which bears the strongest existing evidence. Objective: We intend to assess the role of DOAC in addition to single or dual antiplatelet therapy in subjects with ACS. We will compare the clinical characteristics and explore the efficacy and safety of the DOAC class members (apixaban, betrixaban, dabigatran, edoxaban and rivaroxaban) in terms of reduction in ischemic events in subjects with ACS (ST-segment elevation myocardial infarction [STEMI] or non--ST-segment elevation [NSTEMI]) or subjects who underwent percutaneous coronary intervention (PCI) and or ACS and coexisting atrial fibrillation (AF). Methods: Relevant data will be searched on known data-bases such as Embase, Google Scholar, the Cochrane Central, and PubMed. The trials included will be randomized controlled trials from 2009 to 2022. Subjects will be receiving DOAC for ACS were evaluated for inclusion. The extraction, synthesis, quality, and validity of data will follow the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. The risk of bias tool, version 2.0 (Cochrane) will be used for risk of bias assessment. Data will be pooled using random-effects models. The primary outcome measure will be efficacy end point (composite of cardiovascular death, myocardial infarction, and stroke), while the safety outcome will be minor/major bleeding. Results: We will report the primary efficacy end point risk in the various regimens (DOAC plus SAPT or DAPT) with odds ratio (confidence interval) and both statistical and clinical significance. Further results of risk of bleeding will be compared between the regimens in the subsets of subjects with ACS (e.g. STEMI or NSTEMI) or with comorbid AF or heart failure (HF). Conclusion: We will critically appraise the evidence to support the effects of DOAC plus SAPT or DAPT based on the clinical presentation of subjects. The risk-benefit profile of DOAC will be presented in the two regimens of dual antithrombotic or triple antithrombotic therapy.